The Development of Broadcasting Communication Training Program for Students of MAN 1 Mandailing Natal - Ahmad Salman Farid (PT Agung Media Publisher, 2024)
The Broadcasting Communication Training Program at MAN 1 Mandailing Natal adopts a service learning approach to equip students with specialized skills crucial for navigating the dynamic media and communication landscape. This paper presents the program's design, implementation, and evaluation within a service learning framework. Through a needs assessment, students' interests and baseline skills were identified, guiding the development of a curriculum encompassing public speaking, media production, scriptwriting, and digital content creation. Structured over a semester, the program integrates theoretical knowledge with hands-on practice through weekly sessions. Initial assessments indicate significant enhancements in students' broadcasting competencies and confidence levels post-program. Participants express satisfaction with the practical components, particularly enjoying modules on media production and digital content creation. Moreover, students had opportunities to apply their skills in practical settings, such as school broadcasts and social media projects, thus bridging the gap between theory and real-world application. The positive outcomes suggest the effectiveness of the Broadcasting Communication Training Program in secondary education. Future enhancements may involve integrating advanced training modules, fostering collaborations with local media entities, and leveraging interactive technologies to enrich learning experiences. Continuous evaluation and participant feedback are integral to refining the curriculum, ensuring alignment with student needs and industry advancements.